ZigBee router an implementation of a ZigBee-IP gateway for home-networking - Aguila, Kristel D. (2011)
Presented here is a proposed system that attempts to connect a ZigBee sensor network to the IP network. Since the Internet has in effect become the standard, using it as a means to remotely access the the ZigBee nodes can be a practical solution that addresses problems on accessibility and interoperability of ZigBee networks. In this project, a virtual router in the form of a web server was created to link the sensor network and the IP network. Internet services such as HTTP and FTP were enabled for easier and faster monitoring and collection of ZigBee data. Implemented using C, CGI and HTML, the system allows data translation of TCP/IP to ZigBee and vice versa. The system was tested using two ZigBee modules operating in API or Application Programming Interface mode and can consequently have a wide range of applications in home automation or sensor networking systems.